2014
DOI: 10.4103/0973-7847.134249
|View full text |Cite
|
Sign up to set email alerts
|

Value addition in sesame: A perspective on bioactive components for enhancing utility and profitability

Abstract: Sesame seed is a reservoir of nutritional components with numerous beneficial effects along with health promotion in humans. The bioactive components present in the seed include vital minerals, vitamins, phytosterols, polyunsaturated fatty acids, tocopherols and unique class of lignans such as sesamin and sesamolin. The presence of phenylpropanoid compounds namely lignans along with tocopherols and phytosterols provide defense mechanism against reactive oxygen species and increases keeping quality of oil by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(97 citation statements)
references
References 51 publications
3
94
0
Order By: Relevance
“…Sesame seeds are rich in methylene dioxyphenyl phytochemicals called lignans. Sesame lignans, which play an important role in plant defense, are unique phenolic antioxidants with many health benefits 36. Sesamol (3,4‐methylene dioxyphenol) is a simple phenolic constituent present in sesame oil that reduces free radicals and prevents certain types of cancer, cardiovascular disease, coronary heart disease, stroke, atherosclerosis and other degenerative diseases related to oxidative stress 37.…”
Section: Discussionmentioning
confidence: 99%
“…Sesame seeds are rich in methylene dioxyphenyl phytochemicals called lignans. Sesame lignans, which play an important role in plant defense, are unique phenolic antioxidants with many health benefits 36. Sesamol (3,4‐methylene dioxyphenol) is a simple phenolic constituent present in sesame oil that reduces free radicals and prevents certain types of cancer, cardiovascular disease, coronary heart disease, stroke, atherosclerosis and other degenerative diseases related to oxidative stress 37.…”
Section: Discussionmentioning
confidence: 99%
“…28 The presence of phenylpropanoid compound namely lignan such as sesamin provide adefense mechanism against reactive oxygen species. 29 Kushenol-F, a flavonoid compound, also indicate the complex antioxidant activity. The content of 8-epi-helenalin compounds in this research, was the first reported to be found in propolis.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on the genetic diversity and population structure of germplasm collections is an important foundation for crop improvement and a key component of effective conservation and breeding strategies (Thomson et al, 2007). Pathak et al (2014) have previously reviewed in detail the numerous genetic diversity studies conducted on sesame germplasms. It emerges that sesame harbors a valuable diversity and incongruence between geographical proximity and genetic distance has been reported (Bhat et al, 1999; Laurentin and Karlovsky, 2006; Abdellatef et al, 2008; Pham et al, 2009; Zhang Y. et al, 2012; Alemu et al, 2013; Abate et al, 2015).…”
Section: Application Of Newly Developed “Omics” Tools In Sesame Researchmentioning
confidence: 99%